Retrospective Reports In Organizational Research: A Reexamination Of Recent Evidence - Miller, C. Chet; Cardinal, Laura B.; Glick, William H. (Academy of Management Journal, 1997)
Retrospective reports of important organizational phenomena are commonly fused in strategic management and organization theory research. A recent study, however, suggested that these reports tend to be inaccurate and seriously questioned their use. Our reexamination of this study suggests the situation is not so dire. Our work suggests that retrospective reporting is a viable research methodology if the measure used to generate the reports is adequately reliable and valid. Retrospective reports should neither be rejected nor used indiscriminately.